Public service reforms: issues of accountability and public law / by Dawn Oliver and Gavin Drewry - "Oliver, Dawn" (London, 1996)
This work argues that traditional forms of accountability, based on ministerial responsibility to Parliament, may need to be reassessed, and the new public management matched by a new administrative law.
Keywords: Public utilities-Law and legislation-Great Britain